O trabalho do assistente social na política pública de educação básica na região metropolitana de Porto Alegre - Silveira, Silvia Regina (2013)
This study, guided by the critical-dialectical method, refers to the work of the social worker in Public Policy for Basic Education in the metropolitan area of Porto Alegre, with the problem the following question: How has constituted the work of the social worker in Politics Public Basic Education in the metropolitan region of Porto Alegre. Therefore, the questions that guided the study were: what are the demands met by a social worker? What are the means used to carry out the occupation? What are the products of the work of social policy in this sector? The overall objective was to analyze the work of social workers inserted in Public Policy for Basic Education in the metropolitan region of Porto Alegre in order to contribute to building knowledge in the area of Social Work. Has the following objectives: identify the insertion occurs as social workers in Public Policy for Basic Education, professional activity and the demands met by them and possible coordination with other sectoral policies; know the subject of professional action and strategies for action Social Services in ensuring the right to education; investigate the concept of education used by professional Social Work inserted in Public Policy Basic Education and how their professional activity contributes to the effectiveness of mobilization, participation and protagonism of the subjects. For realization of this study was to survey the presence of the social worker in Public Policy for Basic Education in the metropolitan area of Porto Alegre, where, of the 32 municipalities belonging to the site above, we identified the presence of 16 professionals in the year 2012 , distributed in 07 municipalities. To collect data, we used qualitative research through semi-structured interview, with the approval of the project by the Ethics PUCRS. The research sample was given to 12 professionals. In the treatment of the data analysis was based content Bardin (2006). The main results identified that social workers are included in the Municipal Departments of Education, one of which operates on a Specialized Educational Services Department, said secretary bound. The work of the social worker is carried out based on the axes of access and retention of students in school, being developed 4 shares that constitute instances in management and policy implementation: socioeconomic evaluation, coordination of care networks of other social policies, planning and implementing continuing education meetings to the school community and technical advice to schools. It was concluded that in addition to the activities undertaken to secure access and retention of students in school, social workers are challenged to potentiate the actions related to social emancipatory processes, contributing to the realization of education as a social right with compromised the interests the working class.